MOTIVASI (SELF-TRANSCENDENCE) GURU MA AL-IKHLAS ADDARY DDI TAKKALASI DI MASA PANDEMI COVID-19 - Iqbal, Nabilah Amaliyah (Educational Leadership: Jurnal Manajemen Pendidikan, 2023)
This study, entitled Self-transcendence motivation of Madrasah Aliyah Al-Ikhlas Addary DDI Takkalasi teachers during the Covid-19 pandemic, aims to determine the self-transcendence motivation of Madrasah Aliyah Al-Ikhlas Addary DDI Takkalasi teachers during the Covid-19 pandemic. This study uses qualitative research that is qualitative in nature. descriptive. Data collection techniques used interview and observation techniques at Madrasah Aliyah Al-Ikhlas Addary DDI Takkalasi. The theory used is Maslow's hierarchy of needs theory (Hierarchy of Need). In this theory, there are several needs to motivate educators' performance. In theory, this study finds out the achievement of the spiritual needs of Madrasah Aliyah Al-Ikhlas DDI Takkalasi educators and the hierarchy theory is achieved or fulfilled in the institution so that it can increase the work motivation of educators. The results of the research at Madrasah Aliyah Al-Ikhlas DDI Takkalasi that the role of the Institute in increasing motivation according to Maslow's theory, most of the needs are met even though there are shortcomings in some things, namely the enthusiasm of educators to continue doing charity work. teach with pleasure and sincerity in conveying knowledge which is very important in realizing self-transcendence.